The integration of computational chemistry algorithms into a multimedia environment - Hyde, Richard T. (1996)
Organic chemistry teaching involves the explanation of most phenomena in terms of atomic and molecular models. The main challenge for the student is the creation of mental three-dimensional images of molecules. Unfortunately, many students find the visualisation of the spatial arrangements of molecules a difficult task. For this reason, chemistry teaching has seen the introduction of many innovative teaching tools in an attempt to bring the subject to life for students. Until recently, the cost of computer hardware has prohibited the extensive use of computers within the undergraduate chemistry curriculum. However, the desktop computer has provided a cost-effective platform for developing integrated courseware that presents abstract concepts to the chemistry student.